TRAF3IP2–IL-17 Axis Strengthens the Gingival Defense against Pathogens. (January 2023) - Zhang, J.; Sun, L.; Withanage, M.H.H.; Ganesan, S.M.; Williamson, M.A.; Marchesan, J.T.; Jiao, Y.; Teles, F.R.; Yu, N.; Liu, Y.; Wu, D.; Moss, K.L.; et al.
Recent genome-wide association studies have suggested novel risk loci associated with periodontitis, which is initiated by dysbiosis in subgingival plaque and leads to destruction of teeth-supporting structures. One such genetic locus was the tumor necrosis factor receptor–associated factor 3 interacting protein 2 ( TRAF3IP2 ), a gene encoding the gate-keeping interleukin (IL)–17 receptor adaptor. In this study, we first determined that carriers of the lead exonic variant rs13190932 within the TRAF3IP2 locus combined with a high plaque microbial burden was associated with more severe periodontitis than noncarriers. We then demonstrated that TRAF3IP2 is essential in the IL-17–mediated CCL2 and IL-8 chemokine production in primary gingival epithelial cells. Further analysis suggested that rs13190932 may serve a surrogate variant for a genuine loss-of-function variant rs33980500 within the same gene. Traf3ip2 null mice ( Traf3ip2 –/– ) were more susceptible than wild-type (WT) mice to the Porphyromonas gingivalis –induced periodontal alveolar bone loss. Such bone loss was associated with a delayed P. gingivalis clearance and an attenuated neutrophil recruitment in the gingiva of Traf3ip2 –/– mice. Transcriptomic data showed decreased expression of antimicrobial genes, including Lcn2, S100a8, and Defb1, in the Traf3ip2 –/– mouse gingiva in comparison to WT mice prior to or upon P. gingivalis oral challenge. Further 16S ribosomal RNA sequencing analysis identified a distinct microbial community in the Traf3ip2 –/– mouse oral plaque, which was featured by a reduced microbial diversity and an overabundance of Streptococcus genus bacteria. More P. gingivalis was observed in the Traf3ip2 –/– mouse gingiva than WT control animals in a ligature-promoted P. gingivalis invasion model. In agreement, neutrophil depletion resulted in more local gingival tissue invasion by P. gingivalis . Thus, we identified a homeostatic IL-17-TRAF3IP2-neutrophil axis underpinning host defense against a keystone periodontal pathogen.